Antiviral drugs with immunomodulatory effects role in treatment of anogenital diseases associated with HPV infection - N A Osipova; V N Kustarov; E D Khadzhieva (IP Berlin A.V., 2015)
In the review the role of HPV infection in development of diseases of anogenital area and methods of diagnostics and treatment of HPV infection of anogenital area is considered. Pathogenetic justification of application of preparations with immunomodulatory action is given in complex treatment of the diseases associated with HPV infection.